(untitled) (Bangladesh Journal of Agricultural Research, 2014)
The research activity was conducted in major intensive yard long bean growing areas, such as Jessore, Dhaka, Narsingdi, Comilla, and Chittagong of Bangladesh to know farmers practices (FPs) for managing major insect pests of yard long bean during March 2009 to October 2009 in the farmers fields. The study comprised survey of sample farmers through intensive field visit for field data collection and inspection. A total of 5 farmers practices (FPs) were identified viz., Farmers Practice 1 (FP1) comprised chemicals plus mechanical plus cultural plus field sanitation, FP2 comprised chemicals plus cultural plus field sanitation, FP3 consisted of combination of chemicals plus field sanitation, FP4 having combination of mechanical plus cultural plus field sanitation and FP5 utilized combination of cultural plus field sanitation. Among the sample farmers, 81.33% practiced chemicals plus non-chemical methods, while 18.67% practiced only non-chemical methods. Considering infestation level, pod yield, BCR, and arthropod pests diversity, the performance of FP1 (chemical + mechanical + cultural + field sanitation methods) was adjudged as the best for managing pod borer and aphid and was revealed as the most suitable option (94.10% infestation reduction) for managing major insect pests of yard long bean in those areas of Bangladesh. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20167 Bangladesh J. Agril. Res. 39(1): 173-184, March 2014